1997
DOI: 10.1103/physreva.56.4440
|View full text |Cite
|
Sign up to set email alerts
|

Production of photons by the parametric resonance in the dynamical Casimir effect

Abstract: We calculate the number of photons produced by the parametric resonance in a cavity with vibrating walls. We consider the case that the frequency of vibrating wall is nω 1 (n = 1, 2, 3, ...) which is a generalization of other works considering only 2ω 1 , where ω 1 is the fundamental-mode frequency of the electromagnetic field in the cavity. For the calculation of time-evolution of quantum fields, we introduce a new method which is borrowed from the time-dependent perturbation theory of the usual quantum mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 12 publications
10
72
0
Order By: Relevance
“…The numerical results are entirely in agreement with the analytical predictions derived in [6,8] demonstrating that the numerical simulations are reliable and the method introduced is appropriate to study the dynamical Casimir effect fully numerically.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The numerical results are entirely in agreement with the analytical predictions derived in [6,8] demonstrating that the numerical simulations are reliable and the method introduced is appropriate to study the dynamical Casimir effect fully numerically.…”
Section: Resultssupporting
confidence: 78%
“…The numerically calculated spectra for times t = 25 shown in Fig. 2 are well fitted by the analytical expression N k (t) = (2n−k)k(10 −3 πt) 2 /4 for k < 2n and N k (t) = 0 otherwise [6], predicting a parabolic shape of the particle spectrum. More quantitatively, for n = 2, for instance, the predicted values N 1 (t = 25) = N 3 (t = 25) ∼ 4.63 × 10 −3 , N 2 (t = 25) = 6.17 × 10 −3 agree well with the values N 1 (t = 25) = 4.62 × 10 −3 , N 2 (t = 25) = 6.14 × 10 −3 and N 3 (t = 25) = 4.59 × 10 −3 obtained from the numerical simulations with k max = 50.…”
Section: Numerical Results and Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The corresponding problem for a sphere expanding in the four-dimensional spacetime with constant acceleration is investigated by Frolov and Serebriany [6,7] in the perfectly reflecting case and by Frolov and Singh [8] for semi-transparent boundaries. For more general cases of motion by vibrating cavities the problem of particle and energy creation is considered on the base of various perturbation methods [9,10,11,12,13,14,15,16](for more complete list of references see [16]). It have been shown that a gradual accumulation of small changes in the quantum state of the field could result in a significant observable effect.…”
Section: Introductionmentioning
confidence: 99%